MY SAY: The harsh world of innovation - Abd Razak, Dzulkifli (2009)
Thirty years ago on July 1, a revolution took place in the media world with implications that are still felt today. It was the day the Walkman made its appearance on the world stage. Marketed in 1979 in Japan under the same name, the device is known elsewhere by other names — Soundabout in most places, including the US; Stowaway in the UK; and Freestyle in Sweden.